Experience of Working Women in Managing Stress During Pandemic Using Expressive Art Therapy - Munusamy, Kasturi Bai; Rahman, Mohd Nazri Abdul; Najiha, Amira (Journal of Counseling and Educational Research, 2025)
The COVID-19 pandemic has significantly exacerbated stress levels, particularly among working women in Malaysia, who faced increased domestic and professional responsibilities during the crisis. This study explores the effectiveness of Expressive Art Therapy in managing pandemic-induced stress among this demographic. Through qualitative research involving in-depth interviews with 30 participants, the study investigates how Expressive Art Therapy has been utilized to alleviate emotional and psychological strain. The findings reveal that engaging in activities such as painting, drawing, and dance allows these women to articulate emotions nonverbally, fostering a therapeutic release and promoting mental health resilience. This therapeutic approach has proven beneficial in enhancing emotional well-being, offering an innovative outlet for stress management, and improving overall life satisfaction among participants. The research underscores the potential of Expressive Art Therapy to serve as a valuable tool in occupational stress management strategies, particularly in times of crisis. However, the study acknowledges limitations, including the sample size and the specific focus on women who have opted for this therapy, potentially skewing broader applicability. Future research is recommended to explore Expressive Art Therapy's efficacy in broader demographic settings and to examine its long-term psychological benefits. This study highlights the need for policy enhancements to integrate creative therapies into workplace mental health programs, thus supporting gender-specific mental health needs during unprecedented times.